2023
DOI: 10.3390/s23052487
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Gas/Humidity Sensitivity of the High-Frequency SAW CO Gas Sensor Based on Noble-Metal-Modified Metal Oxide Film

Abstract: In order to improve the response characteristics of the surface acoustic wave (SAW) sensor to trace gases, a SAW CO gas sensor based on a Pd–Pt/SnO2/Al2O3 film with a high-frequency response performance is proposed in this paper. The gas sensitivity and humidity sensitivity of trace CO gas are tested and analyzed under normal temperatures and pressures. The research results show that, compared with the frequency response of the Pd–Pt/SnO2 film, the CO gas sensor based on a Pd–Pt/SnO2/Al2O3 film has a higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies in this area have shown that reactive properties and negative differential resistance are inextricably linked, and the versatility and simplicity of radio electronic devices based on transistor structures with negative resistance is the prospect of their practical use. Self-oscillating parametric humidity sensors that implement the "humidityfrequency" conversion principle are characterized by simplicity and versatility, as well as accuracy and noise immunity [6,7,22].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…Studies in this area have shown that reactive properties and negative differential resistance are inextricably linked, and the versatility and simplicity of radio electronic devices based on transistor structures with negative resistance is the prospect of their practical use. Self-oscillating parametric humidity sensors that implement the "humidityfrequency" conversion principle are characterized by simplicity and versatility, as well as accuracy and noise immunity [6,7,22].…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%